Obsolescence of the cited references: An academic myth persistent on the Venezuelan college research - Arias, Fidias G. (2016)
This article analyses an academic myth that affects the development of research in the venezuelan collegiate means, specifically in the social science and liberal arts. It is about the belief of tutors and thesis students on the obsolescence of the references cited 5 years after being published. Based on quantitative approach, a documental and field research was made where 160 people were surveyed, 90 thesis students and 70 tutors of graduate and postgraduate studies in social and humanities fields from public and private venezuelan college institutions. The statistical results reflect that most surveyed people express that the cited references must have been published in the past 5 years. However, when they were asked about the existence of a norm, they said they had no knowledge on both aspects. Later, as product of documentary analysis of the literature and research on bibliometrics, the existing myth is refuted.